Entering the Malaysian Market: PT. Rendang Uni Tutie B2B Strategy - Agatha, Fathia; Komaladewi, Rita (Golden Ratio of Mapping Idea and Literature Format, 2026)
The internationalization of micro, small, and medium enterprises (MSMEs) in the food and beverage sector is becoming increasingly relevant due to regional integration and evolving cross-border consumption patterns. This study analyzes the case of PT. Rendang Uni Tutie, an Indonesian MSME specializing in Minangkabau rendang, and its entry into the Malaysian market through a business-to-business (B2B) approach. Using a mixed-method case study, the research integrates primary data from purposive interviews, observations, and documentation with secondary data from official statistics and trade reports. Strategic assessments were conducted through PESTEL, SWOT, IFAS, EFAS, and strategy matrix frameworks to evaluate both internal and external conditions. The findings reveal that PT. Rendang Uni Tutie possesses substantial internal strengths, including authentic product quality, shelf life of up to two years, premium multilingual packaging, and certification from Halal MUI, BPOM, and HACCP. These strengths support competitiveness in export markets. Externally, Malaysia’s Muslim-majority population, cultural familiarity with rendang, regional trade agreements (AFTA, ATIGA), and strong digital infrastructure provide favorable conditions for expansion. Nevertheless, challenges persist, particularly the absence of JAKIM halal certification, relatively high logistics costs, and limited digital marketing capacity. The SWOT analysis positions the company in Quadrant I, emphasizing the need for aggressive SO strategies, such as leveraging certifications as trust capital, optimizing benefits from trade liberalization, and forming B2B partnerships with local distributors and e-commerce platforms. Overall, this research contributes to the literature on SME internationalization and digital B2B strategies while offering practical recommendations for strengthening the global competitiveness of Indonesian food MSMEs.